Bioactive natural products : detection, isolation, and structural determination / [Edited by] Steven M Colegate; Russell J Molyneux - Colegate, Steven M.edited
Following the successful format of the first edition, "Bioactive Natural Products: Detection, Isolation, and Structural Determination, Second Edition" presents the most recent techniques for the detection, isolation, and structural determination of bioactive natural products. This second edition features new case studies and illustrations that demonstrate practical applications of some of the techniques covered in the book. The text includes infrared methods like Fourier transform and near infrared reflectance, ultraviolet spectroscopic methods, gas chromatography and liquid chromatography linked with mass spectrometry, combinatorial chemistry approaches, high-throughput approaches, bioactive chemical extraction, and novel bioassay development.